ANALISIS IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) STUDI PADA PT VIVASTOR TECHNO LOGICA SEBAGAI PENGEMBANG APLIKASI LUMBUNG GEOAPPLIANCE - , I Gusti Ayu Arida Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was motivated by the lack of customer loyalty and there are complaints from customers to PT Vivastor Techno Logica. So the company needs to create a program in which to solve the above problems. Customer Relationship Management ( CRM ) is the selected program to increase customer satisfaction by improving relationships between clients and developer as well as resolve customer complaints. Framework of CRM includes the design and strategy of the organization in accordance with the CRM design, CRM implementation analysis and execution of interactions with customer. The research method used was a qualitative research method. Technique of data collection was conducted by using interview technique. Researcher conducted interviews with three informants, namely the first of the top level management, develop, and implementation team. The results showed that the company already has had a high organizational readiness for implementing CRM. It can be seen from the vision and mission of the company that focus on customer. In terms of CRM implementation, the company already has a team with diverse backgrounds and competencies required by the customer. But in terms of execution team, the company still needs to improve its interaction with the customers.